Excessive Iron Availability Caused by Disorders of Interleukin-10 and Interleukin-22 Contributes to High Altitude Polycythemia - Liu, Yun-Sheng; Huang, He; Zhou, Si-Min; Tian, Huai-jun; Li, Peng (Frontiers in Physiology, 2018)
Background: Because the pathogenesis of high altitude polycythemia (HAPC) is unclear, the aim of the present study was to explore whether abnormal iron metabolism is involved in the pathogenesis of HAPC and the possible cause. Methods: We examined the serum levels of iron, total iron binding capacity, soluble transferrin receptor (sTfR), ferritin and hepcidin as well as erythropoietin (EPO) and inflammation-related cytokines in 20 healthy volunteers at sea level, 36 healthy high-altitude migrants and 33 patients with HAPC. Mice that were exposed to a simulated hypoxic environment at an altitude of 5000 m for four weeks received exogenous iron or intervention on cytokines, and the iron-related and hematological indices of peripheral blood and bone marrow were detected. The in vitro effects of some cytokines on hematopoietic cells were also observed. Results: Iron mobilization and utilization were enhanced in people who had lived at high altitudes for a long time. Notably, both the iron storage in ferritin and the available iron in the blood were elevated in patients with HAPC compared with the healthy high-altitude migrants. The correlation analysis indicated that the decreased hepcidin may have contributed to enhanced iron availability in HAPC, and decreased interleukin (IL)-10 and IL-22 were significantly associated with decreased hepcidin. The results of the animal experiments confirmed that a certain degree of iron redundancy may promote bone marrow erythropoiesis and peripheral red blood cell production in hypoxic mice and that decreased IL-10 and IL-22 stimulated iron mobilization during hypoxia by affecting hepcidin expression. Conclusion: These data demonstrated, for the first time, that an excess of obtainable iron caused by disordered IL-10 and IL-22 was involved in the pathogenesis of some HAPC patients. The potential benefits of iron removal and immunoregulation for the prevention and treatment of HAPC deserve further research.